Hot Wheels : to the extreme - Harper, Benjamin; Wisinski, Ed; White, Dave, 1973- (New York : Scholastic, 2007)
An easy reader with illustrations of some extreme cars.
Keywords: Automobiles -- Juvenile fiction; Hot Wheels toys -- Juvenile fiction